2015
DOI: 10.17265/2161-6256/2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The Main Causes of Calf Mortality in Dairy Farms in Poland

Abstract: Calf mortality is one of important problems of calf rearing in dairy farms worldwide. Besides, several noninfectious factors, such as management around birth, colostrum management, calf housing, feeding system, hygiene and pathogens, play an important role in calf rearing. The aim of the study was to show the most common causes of mortality of calves up to 90 d of their lives. Some data are available concering calf rearing management on small and medium size dairy farm typical for Polish regions. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…Additionally, the incidence of respiratory disorders in this group reached 18%. Our results correspond with those reported by Żychlińska-Buczek et al (2015), but are higher than those noted by Svensson et al (2006) and Gulliksen et al (2009). In contrast, the incidence of diarrhea and upper respiratory tract infections in TRT calves was 40% and 33%, respectively, supporting a positive effect of colostrum-supplemented transition milk on the health status of calves.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, the incidence of respiratory disorders in this group reached 18%. Our results correspond with those reported by Żychlińska-Buczek et al (2015), but are higher than those noted by Svensson et al (2006) and Gulliksen et al (2009). In contrast, the incidence of diarrhea and upper respiratory tract infections in TRT calves was 40% and 33%, respectively, supporting a positive effect of colostrum-supplemented transition milk on the health status of calves.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, the number of calves that died due to enteric and respiratory diseases together was 4 calves all of them with FPT (Figure 2). These results were consistent with those reported by Żychlińska-Buczek et al (2015) who indicated that during the first 90 days of old the main cause of death was diarrhea, the respiratory disorders being the next common cause of loss of calves. Hulbert and Moisá (2016) noted that the mortality rate among calves in the United States was high, with more than half of deaths due to diarrhea.…”
Section: The Relationship Between Serum Igg Levels and Mortality Ratesupporting
confidence: 93%
“…A high event of diarrhea is due to poor quality of the colostrum given to the newborn calf, which results in a failure of passive immune transfer (FPT). Also, Żychlińska-Buczek et al (2015) confirmed that 80% of cases of disease during the preweaning period are disorders of diarrhea and respiratory syndrome which were the major cause of business failure and economic losses.…”
Section: The Relationship Between Serum Igg Levels and Morbidity Ratementioning
confidence: 78%
“…The proportion of both Nematode (OR=5.7, p< 0.05) and Eimeria species (OR=5.3, P< 0.05) infection was significantly higher in diarrheic calves than calves with normal faeces consistency. In dairy farms diarrhea was most frequently observed disorder in various parts (Tamrat et al, 2020;Żychlińska-Buczek et al, 2015;Megersa et al, 2009;Wudu et al, 2008). It is known that some Nematodes species and Eimeria species known to damage the intestinal epithelial cells leading to inflammation and cause diarrhea (Constable et al, 1017;Ramadan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%